Perceived Teachers’ Expectations, Self-Esteem And Reflective Thinking Skills Among Talented Students In Saudi Arabia - Al Shammari, Talal Ibrahim A (2020)
The intention of this study is to investigate Perceived Teachers’ Expectation, Self-esteem, and Reflective Thinking Skills among Talented Students in Saudi Arabia. Sample of 300 students from six (6) schools located in the Northern Borders of Saudi Arabia who were assigned to Saudi’s Mawhibbah programme were recruited as participants in this study. Data for perceived teachers’ expectations was collected through perceived teachers’ expectations scale, whereas the Rosenberg self-esteem scale, was used to collect data regarding participants’ self-esteem. Students’ reflective thinking skills was measured using the reflective thinking skills scale. Qualitative data were collected using semi-structured interviews. The study results showed that perceived teachers’ expectations academically significantly influence the self-esteem and reflective thinking skills of talented students in Saudi Arabia. However, perceived teachers’ expectations disciplinary did not have any significantly influence on both self-esteem skills as well as reflective thinking skills of talented students in Saudi Arabia. On the other hand, students’ self-esteem mediates the causal relationship between perceived teachers’ expectations and reflective thinking skills. Qualitatively, the participants presented varying perspectives on perceived teachers’ expectations, and thus, they reacted differently towards similar education system. Number of the participants developed their reflective thinking skills because they perceived that despite expecting them to achieve high performance, their teachers do not usually provide them with adequate support. Therefore, their reflective thinking skills suggested that they should seek answers from multiple sources. In the context of the current study, self-esteem challenge varies. However, the most dominant challenge is the shift of the ideal self from being a religious and obedient individual into a smart and problem-solving individual who can live independently. This shift drives the participants to improve their reflective thinking skills through willingness to learn, critical thinking and resourcefulness at the cost of being less obedient and religious. The study has a made significant contribution to theory where it relates the reflective thinking skills with the perceived teachers’ expectations through the intervention of self-esteem as mediator. Thus, the talented programme of Saudi Arabia must maintain and enhance their students’ self-esteem. Subsequently, self-esteem mediates the effect of perceived teachers’ expectations on reflective thinking skills among talented students. Therefore, improving students’ self-esteem also indirectly increases their reflective thinking skills.